2021
DOI: 10.3390/brainsci11020181
|View full text |Cite
|
Sign up to set email alerts
|

Do ADHD Symptoms, Executive Function, and Study Strategies Predict Temporal Reward Discounting in College Students with Varying Levels of ADHD Symptoms? A Pilot Study

Abstract: The purpose of this study was to examine the relationship between temporal reward discounting and attention deficit hyperactivity disorder (ADHD) symptoms in college students. Additionally, we examined whether temporal reward discounting was associated with executive functioning in daily life and with learning and study strategies in this group. Thirty-nine college students (19 with ADHD and 20 controls) participated after meeting criteria for ADHD or non-ADHD based on standardized assessment. Strong preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In a pilot study by Scheres and Solanto [193], steep TD was not only associated with combined type ADHD, specifically the hyperactivity-impulsivity symptom domain, but also with poor utilisation of learning and/or study skills. TD was therefore postulated to be an important target for EF interventions for university students with or without ADHD [193], more so for interventions that were designed to activate and sustain motivation to pursue a long-term goal for a reward, such as pursuing and completing a university degree [194]. Findings like this could be useful for enhancing the effectiveness of CBT based interventions for university students with ADHD like the ACCESS program, by for example, tailoring EF interventions to also target TD.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 93%
See 1 more Smart Citation
“…In a pilot study by Scheres and Solanto [193], steep TD was not only associated with combined type ADHD, specifically the hyperactivity-impulsivity symptom domain, but also with poor utilisation of learning and/or study skills. TD was therefore postulated to be an important target for EF interventions for university students with or without ADHD [193], more so for interventions that were designed to activate and sustain motivation to pursue a long-term goal for a reward, such as pursuing and completing a university degree [194]. Findings like this could be useful for enhancing the effectiveness of CBT based interventions for university students with ADHD like the ACCESS program, by for example, tailoring EF interventions to also target TD.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 93%
“…Temporal discounting (TD) describes how the subjective value of a reward significantly declines when the said reward is delayed [192]. In a pilot study by Scheres and Solanto [193], steep TD was not only associated with combined type ADHD, specifically the hyperactivity-impulsivity symptom domain, but also with poor utilisation of learning and/or study skills. TD was therefore postulated to be an important target for EF interventions for university students with or without ADHD [193], more so for interventions that were designed to activate and sustain motivation to pursue a long-term goal for a reward, such as pursuing and completing a university degree [194].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…This tendency is found across development, including in adulthood [ 9 , 12 , 13 ]. Such a pattern of choice between rewards is related to a range of negative outcomes, including criminality, substance use, and greater functional impairment, such as in time and money management [ 14 ] as well as in learning and study strategies [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bidirectional link of substance use disorder (SUD) and attention-deficit/hyperactivity disorder (ADHD) is widely described [ 1 , 2 , 3 , 4 ], although its nature remains unclear [ 5 ]. ADHD, a neurodevelopmental disorder characterized by inattentive or hyperactive/impulsive behavior, or both [ 6 ], is associated with impairment in multiple life domains [ 7 , 8 , 9 ]. A meta-analysis found that 23.1% of those seeking SUD treatment have ADHD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%